Edukasi Penggunaan Internet Aman dan Sehat untuk Anak Usia Dini di Desa Muara Penimbung - Christian Damar Sagara Sitepu; Rochmawati Daud; Meita Rahmawati; Vivi Usmayanti (PT. Altaf Publishing Corp, 2025)
The increasingly widespread use of the internet among the community, including early childhood, requires special attention to safety and health in accessing the digital world. This community service aims to provide education on safe and healthy internet use to early childhood in Muara Penimbung Village. This activity includes an active participation-based approach, where children, parents, and educators are involved in understanding the potential benefits and risks of the internet. This program includes counseling, interactive training, and simulations of real-life situations designed to improve digital literacy, build awareness of personal data protection, and teach how to avoid negative content. The results of this activity show an increase in participants' understanding of the importance of supervision and guidance when children access the internet. With this program, it is hoped that a safer and healthier digital ecosystem will be created for children in Muara Penimbung Village, as well as being a model to be implemented in other areas